A Novel Mutation in the Mitochondrial DNA Cytochrome b Gene (MTCYB) in a Patient with Prader Willi Syndrome. (March 2015) - Yiş, Uluç; Ezgü, Fatih Süheyl; Karakaya, Pakize; Polat, İpek and Arslan, Nur and Çankaya, Tufan and Bozkaya, Özlem Giray and Kurul, Semra Hız
In recent years, it has been suggested that defects in energy metabolism may accompany Prader Willi syndrome. Mutations in the mitochondrial cytochrome b gene have been commonly associated isolated mitochondrial myopathy and exercise intolerance, rarely with multisystem disorders. The authors describe a novel mutation (mt. 15209T>C) in mitochondrial cytochrome b gene in a 2-year-old girl with Prader-Willi syndrome with a clinical history of lactic acidosis attacks, renal sodium loss, hepatopathy, progressive cerebral atrophy, and sudden death. The authors suggest that atypical clinical findings in patients with Prader-Willi syndrome should direct the physician to search for a mitochondrial disease.